THEORETICAL FOUNDATIONS OF VERBS OF SOCIAL RELATIONS IN ENGLISH AND UZBEK LANGUAGES (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the theoretical foundations of verbs of social relations in English and Uzbek from cognitive, semantic, sociolinguistic, and comparative-typological perspectives. Verbs of social relations are defined as lexical units that encode interpersonal interactions, social hierarchy, and communicative intentions. The purpose of this study is to identify the structural, semantic, and pragmatic features of such verbs in both languages and to determine their similarities and differences.The findings show that although English and Uzbek share universal semantic characteristics, they differ significantly in expressing social meanings due to typological and cultural factors. These results contribute to a deeper understanding of cross-linguistic variation and provide useful insights for language teaching and translation studies.